Alimentación complementaria y caries en infantes de 3 a 5 años de la I.E. Barcia Boniffatti 2024 - Ramirez Lopez, Leslie Mirella (2024)
OBJECTIVE: The general objective of this thesis is to determine the relationship between the start time and frequency of complementary feeding with the prevalence of dental caries in infants from 3 to 5 years of age. Barcia Boniffatti in 2024. METHODOLOGY: The study used a quantitative approach, non-experimental, descriptive and correlational design, with a sample of 143 randomly selected children. Questionnaires were applied to parents to collect information on eating habits and the CEOD index to measure the prevalence of caries. RESULTS: The results showed that 74.1% of the infants began complementary feeding at 6 months, while 53.8% were fed between 2 to 3 times a day. Regarding the prevalence of cavities, 62.2% of children had at least one cavity, and a small percentage had multiple cavities, which indicates the severity of the problem in some cases. CONCLUSIONS: The conclusions indicate that there is a correlation between the time and frequency of complementary feeding with the prevalence of dental caries. An early start or a greater frequency of feeding, without accompanied by adequate oral hygiene, could be associated with a greater risk of developing cavities. These results highlight the importance of educating parents and caregivers about dietary and oral hygiene practices for the prevention of caries in childhood.